CD4+ T cell count in HIV/TB co-infection and co-occurrence with HL: Case report and literature review - Xiao Pingping; Chen Xuyan; Chen Yongquan; Fan Wei; Dong Zhigao; Huang Jinmei; Zhang Yi (Open Life Sciences, 2023)
In the human immunodeficiency virus (HIV)-infected population, especially HIV with concomitant tuberculosis (TB) or Hodgkin’s lymphoma (HL), numerous risk factors have been reported in recent years. Among them, the decreased CD4+ T cell count was recognized as the common risk factor. We report a case of a patient with HIV and TB and HL co-occurrence, in which patient’s CD4+ T cell count was inconsistent with disease. A 58-year-old male presented with fever and shortness of breath that persisted for 2 months. The patient had a 4-year history of HIV infection and underwent antiretroviral therapy (ART) effectively. After blood test, computed tomography, bone biopsy, and lymphoma biopsy, the patient was diagnosed with skeletal TB and HL, underwent TB treatment and received ART, and underwent four cycles of chemotherapy. CD4+ T cell count was not decreased before diagnosed with TB/HL and increased in this case after the fourth cycle of chemotherapy. We collected and analyzed CD4+ T cell counts in our case and reviewed relevant literature. It is suggested that CD4+ T cell count may be insufficient to predict the risk of HIV-related disease, especially lymphoproliferative disorders.